THE EFFECT OF IMPLEMENTATION OF INQUIRY LEARNING MODEL TO THE RESULTS OF SCIENCE LEARNING OF FIFTH GRADE STUDENTS SDN 18 PEKANBARU - Tifany Hidayat; M. Jaya Adi Putra; Zariul Antosa (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2019)
The background of this study is learning outcomes of students of SDN 18 Pekanbaru, it is known that has not reached the value according to the standard score which is 75. This research aims to determine how the application of inquiry learning models to science learning outcomes of fifth grade students of SDN 18 Pekanbaru. This research was a quasi-experimental study with pretest and two groups (experimental group and control group). The experimental group was the group given inquiry treatment model. Based on the results of the experiment, it was found that there was an effect of the implementation of inquiry learning models on science learning outcomes of fifth grade students of SDN 18 Pekanbaru It is known that the t test is higher than t on table (4.60> 2,006), the research hypothesis which says there is an effect of the implementation of inquiry learning model to the results of science learning of fifth grade students of SDN 18 Pekanbaru, is accepted